THE INFLUENCE OF SPIRITUALITY IN THE WORKPLACE, TRUST, AND TRANSFORMATIONAL LEADERSHIP ON AUDITOR PERFORMANCE - Audita Setiawan; Nandan Limakrisna; Lucy Warsindah (Multifinance, 2026)
This study examines the effects of workplace spirituality, trust, and transformational leadership on employee performance, with organizational commitment serving as a mediating variable. The research was conducted among auditors working in Public Accounting Firms in West Java, Indonesia. Using a quantitative approach, data were collected from 202 auditors through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that workplace spirituality, trust, and transformational leadership have significant positive effects on organizational commitment. Trust and transformational leadership directly influence employee performance, while workplace spirituality does not show a direct effect on performance. However, organizational commitment partially mediates the relationship between all three antecedent variables and employee performance. These findings highlight the importance of strengthening psychological and behavioral factors within audit organizations to enhance commitment and performance. The study contributes to the literature by integrating spiritual, relational, and leadership factors into a single structural model within the auditor profession context.